2014
DOI: 10.1016/j.euroneuro.2014.06.002
|View full text |Cite
|
Sign up to set email alerts
|

The TOMM40 poly-T rs10524523 variant is associated with cognitive performance among non-demented elderly with type 2 diabetes

Abstract: The variable length poly-T, rs10524523 (‘523’) located within the TOMM40 gene, was recently associated with several phenotypes of cognitive function. The short (S) allele is associated with later AD onset age and better cognitive performance, compared to the longer alleles (long and very-long (VL)). There is strong linkage disequilibrium between variants in the TOMM40 and APOE genes. In this study, we investigated the effect of ‘523’ on cognitive performance in a sample of cognitively normal Jewish elderly wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 36 publications
(72 reference statements)
3
18
0
Order By: Relevance
“…We further included an additional group of clinical variables as covariates in the analysis (mean hemoglobin A1c level, systolic and diastolic blood pressure, creatinine level, total cholesterol, triglycerides, HDL and LDL level, BMI and T2D medication). Adjusting for these cardiovascular covariates is consistent with our previous genetic studies in this cohort (Greenbaum et al, 2014; Ravona-Springer et al, 2013), and based on evidences that these factors are associated with cognitive decline and dementia (Beeri et al, 2009). We also added the carriership status of the APOE ε4 allele as a covariate, to account for a possible effect on cognition.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We further included an additional group of clinical variables as covariates in the analysis (mean hemoglobin A1c level, systolic and diastolic blood pressure, creatinine level, total cholesterol, triglycerides, HDL and LDL level, BMI and T2D medication). Adjusting for these cardiovascular covariates is consistent with our previous genetic studies in this cohort (Greenbaum et al, 2014; Ravona-Springer et al, 2013), and based on evidences that these factors are associated with cognitive decline and dementia (Beeri et al, 2009). We also added the carriership status of the APOE ε4 allele as a covariate, to account for a possible effect on cognition.…”
Section: Discussionsupporting
confidence: 89%
“…Similarly to our previous studies (Greenbaum et al, 2014; Ravona-Springer et al, 2013), factor analysis revealed four cognitive domains, which were then scored as totals of z scores: episodic memory factor (included word list immediate and delayed recall, and recognition from the CERAD (Consortium to Establish a Registry for Alzheimer’s Disease) performance neuropsychological battery), semantic categorization factor (included the letter and category fluency, and similarities), attention/working memory factor (included the diamond cancellation test, digit span forward and backward), and an executive factor (included the trails making A and B and the digit symbol test). In addition, an overall cognition measure was created by summarizing the four domains.…”
Section: Methodssupporting
confidence: 84%
“…For the TOMM40 ′523 interaction term, we restricted the sample to only those participants who were APOE ε3 homozygous. We did so because the S allele is associated with poorer cognitive outcomes in APOE ε3 heterozygotes [2729,44]. This restriction also helped to nullify any effect that the APOE ε2 and ε4 alleles might have had on cortical thickness in TOMM40 analyses [2729,44].…”
Section: Methodsmentioning
confidence: 99%
“…We did so because the S allele is associated with poorer cognitive outcomes in APOE ε3 heterozygotes [2729,44]. This restriction also helped to nullify any effect that the APOE ε2 and ε4 alleles might have had on cortical thickness in TOMM40 analyses [2729,44]. Additionally, because the L allele is in high linkage disequilibrium with the ε4 allele (i.e., recombination occurs at different frequencies than if there was random assortment), and therefore the alleles' effects are not separable statistically, we compared people with the VL/VL genotype to people with the S/S genotype [29].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation